2004
DOI: 10.1071/rdv16n1ab69
|View full text |Cite
|
Sign up to set email alerts
|

69dolly: A Final Report

Abstract: The ability to produce cloned livestock using postmortem tissue could incorporate an additional application into the field of nuclear transfer. This study examined the feasibility of producing cloned cattle using a primary cell line established from a postmortem beef carcass. A market beef heifer processed at a USDA-certified slaughterhouse was used to develop a primary somatic cell line. Tissue samples were taken from the kidney and forelimb regions either 1) immediately following slaughter (fresh) or 2) 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Oversized cloned offspring add to the birth complications. They are larger than IVP, artificially inseminated or naturally-mated controls (52). It has been reported that somatic cloned calves are heavier than embryonic clones (21).…”
Section: Parturition Difficultiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Oversized cloned offspring add to the birth complications. They are larger than IVP, artificially inseminated or naturally-mated controls (52). It has been reported that somatic cloned calves are heavier than embryonic clones (21).…”
Section: Parturition Difficultiesmentioning
confidence: 97%
“…Telomeres are regions of DNA at the ends of chromosomes which progressively shorten after each cell division in most somatic cell types. Whilst Dolly may have developed arthritis and was euthanised at a relatively young age because of a virallyinduced lung tumour (52), this may have resulted from her largely indoor housing and handling rather than the fact that she was a clone. Other studies have been contradictory with regard to telomere length in clones, with reports of restoration to normal in cattle (3,64) and mice (69) and even instances of extended telomere lengths (32).…”
Section: Clone-specific Phenotypesmentioning
confidence: 99%
“…Such problems tend to disappear after 1 year of age. Finally, the report on Dolly's death indicated that she died of Jaagsiekte sheep retrovirus infection, but that she was previously healthy (apart from arthritis, which was treated with anti-inflammatory drugs) and fertile (Rhind et al, 2004).…”
Section: Fetal Developmentmentioning
confidence: 99%
“…The conference abstract by Rhind et al . 1 reported that Dolly 2 had OA of the left stifle (knee) at 5½ years of age. Radiographs of her right stifle were reportedly normal at that stage.…”
Section: Introductionmentioning
confidence: 99%